A study of cis-trans isomerisation of the bis-chelated complexes of platinum (II) and palladium (II) with N,N-dialkyl-N'aroyl(acyl)thiourea ligands - Hanekom, Dirk C. (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc) -- University of Stellenbosch, 2006.